Beyond the Colonial Phantasmagoria; Rethinking the Idea of Secular, Secular Criticism and Islam - Ali Jauhar Changarath (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The tendencies of recalling and rethinking identity formation while remaining in the liminal space of the colonial matrix, are themselves the constructs of a particular language in itself. The decolonial theory was formed as part of standing beyond this particular language. In this perspective we can see numerous works conceptualizing the notions of meta-narratives outside the colonial matrix. This paper explores such dialogues and interpretations towards secularism and secular critic and approaches which place them in a broad sense of religion beyond the colonial perspective.